Priestly power that empowers: Michel Foucault, middle-tier Levites, and the sociology of popular religious groups in Israel - Christian, Mark A. (The journal of Hebrew scriptures, 2009)
The task of reconstructing the religious history of Israel can only be accomplished incrementally. Regarding methodology, if one chooses to engage the complexities of, say, the Israelite priesthood, synchronic analysis alone does not reveal its stages of development. Meticulous redactional analysis moreover exposes only aspects or phases of the sophisticated historiographies of the major writers in the preexilic, exilic, and postexilic periods and their grand schemas. One method of penetrating the pretense of uniformity is to approach the material through the use of analogy. Michel Foucault's work on power and knowledge informs the present study, in particular his concept of the distribution of power by “specialists.” The Levites' conflicted story needs no introduction, and its comprehensive transcription is not attempted here. Rather, drawing from biblical and wider ancient Near Eastern evidence, their activities as middle-tier “specialists” are outlined. The Levite in many instances locates professionally and socially between elite priests (living in larger cities) and populace (living in residential towns and villages). It is the itinerant, often times prophetically-infused Levite who, while maintaining the most contact with the general population, must at the same time maintain a viable connection with central authorities. Because his situation often necessitates collaboration with laity of dubious lineage, the Levite's priestly power turns out to be one that empowers.